Gerak Dasar Tari Untuk Anak Usia Dini - Jauhari Kumara Dewi (Insititut Agama Islam Negeri (IAIN) Curup, 2020)
Early childhood education is the embryo of an educational process that seeks to develop several aspects of development, including art. Art is one that cannot be separated in human life. The movements that are carried out in children every day are very effective means of physical development, namely developing children's motor skills. As we already know that children's motor skills include gross motor development and fine motor development. So it is very important to recognize dance movements in early childhood, in developing gross motor skills. So that early childhood can express themselves and be able to appreciate the diversity of arts as a form of respect for art. This paper aims to describe the implementation of learning the basic movements of dance in developing gross motor skills for early childhood